Percepç\~oes sobre a regulamentaç\~ao do lobby no Brasil: Convergências e divergências - Manoel Leonardo Santos; Lucas Cunha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper aims to empirically verify to what extent the controversies on lobbying regulation are manifested by the opinions of political actors directly involved in the activities of the National Congress, which are interest groups' representatives and legislative advisors of governmental agencies. To this end, we present results of original survey and in-depth interviews. The results point to convergence on the need to regulate lobbying activity and about the positive effects expected to come with regulation. We also find convergence with most regulatory initiatives presented in the Congress. However, differences appear when the most controversial themes are addressed, especially those on accountability and declaration of interest on the part of pressure groups. It thus concludes that the political opinion amongst actors engaged in the representation of interests within the Congress is supportive of the regulations, but some points should be taken to further debate. It is recommended that this debate must not ignore that lobbying is an important mechanism of political participation and that it depends, largely, on the access of different social groups to the constituted power and its representatives.
Keywords: D72; 330; lobbying; regulation; interest groups; Congresso Nacional